Surfactants and Interfacial Phenomena - Rosen, Milton J; Kunjappu, Joy T (Wiley, 2012)
Now in its fourth edition, Surfactants and Interfacial Phenomenaexplains why and how surfactants operate in interfacial processes (such as foaming, wetting, emulsion formation and detergency), and shows the correlations between a surfactant's chemical structure and its action.Updated and revised to include more modern information, along with additional three chapters on Surfactants in Biology and Biotechnology, Nanotechnology and Surfactants, and Molecular Modeling with Surfactant Systems, this is the premier text on the properties and applications of surfactants.This book provides an easy-to-read, user-friendly resource for industrial chemists and a text for classroom use, and is an unparalleled tool for understanding and applying the latest information on surfactants.   Problems are included at the end of each chapter to enhance the reader’s understanding, along with many tables of data that are not compiled elsewhere.  Only the minimum mathematics is used in the explanation of topics to make it easy-to-understand and very user friendly.